Finite Mixture Models for Linked Survey and Administrative Data: Estimation and Post-estimation - Stephen P. Jenkins; Fernando Rios-Avila (Institute of Labor Economics (IZA), 2021)
Researchers use finite mixture models to analyze linked survey and administrative data on labour earnings (or similar variables), taking account of various types of measurement error in each data source. Different combinations of error-ridden and/or error-free observations characterize latent classes. Latent class probabilities depend on the probabilities of the different types of error. We introduce a set of Stata commands to fit a general class of finite mixture models to fit to linked survey-administrative data We also provide post-estimation commands for assessment of reliability, marginal effects, data simulation, and prediction of hybrid earnings variables that combine information from both data sources.
Keywords: C81; C83; D31; 330; linked survey and administrative data; measurement error; finite mixture models